Evaluasi Laik Fungsi Jalan Menggunakan Pemeringkatan Skala Bintang Pada Ruas Jalan Masjid Raya, Kota Makassar - Vefryany Enjelyn Layuk (Paulus Civil Engineering Journal, 2025)
Roads are a crucial transportation infrastructure that plays a significant role in various community activities in both urban and rural areas. Article 30 of Indonesian Law number 38 of 2004 concerning Roads stipulates that public roads are operated after being determined to meet the technical and administrative requirements for road functionality. The objective of this research is to determine the star rating score for the road functionality of national urban roads. The guideline used in this study is 06/P/BM/2024. The star rating assessment is based on segments with intervals of 100 meters. Star rating is an objective assessment of the likelihood and severity of accidents occurring on the road. The research results on Masjid Raya Road, Makassar City, show star ratings of 5 and 4, indicating safer and safe roads.